Nutritional and metabolic requirements for the infection of HeLa cells by Salmonella enterica serovar Typhimurium. - Steven D Bowden; Amanda C Hopper-Chidlaw; Christopher J Rice; Vinoy K Ramachandran; David J Kelly; Arthur Thompson (PLoS ONE)
Salmonella is the causative agent of a spectrum of human and animal diseases ranging from gastroenteritis to typhoid fever. It is a food--and water--borne pathogen and infects via ingestion followed by invasion of intestinal epithelial cells and phagocytic cells. In this study we employed a mutational approach to define the nutrients and metabolic pathways required by Salmonella enterica serovar Typhimurium during infection of a human epithelial cell line (HeLa). We deleted the key glycolytic genes, pfkA and pfkB to show that S. Typhimurium utilizes glycolysis for replication within HeLa cells; however, glycolysis was not absolutely essential for intracellular replication. Using S. Typhimurium strains deleted for genes encoding components of the phosphotransferase system and glucose transport, we show that glucose is a major substrate required for the intracellular replication of S. Typhimurium in HeLa cells. We also deleted genes encoding enzymes involved in the utilization of gluconeogenic substrates and the glyoxylate shunt and show that neither of these pathways were required for intracellular replication of S. Typhimurium within HeLa cells.